A Study on the Bandwidth Characteristics of Pleated Pneumatic Artificial Muscles. Issue 1 (13th May 2009) - Versluys, Rino; Deckers, Kristel; Van Damme, Michaël; Van Ham, Ronald; Steenackers, Gunther; Guillaume, Patrick; Lefeber, Dirk
Abstract : Pleated pneumatic artificial muscles have interesting properties that can be of considerable significance in robotics and automation. With a view to the potential use of pleated pneumatic artificial muscles as actuators for a fatigue test bench (high forces and small displacements), the bandwidth characteristics of a muscle-valve system were investigated. Bandwidth is commonly used for linear systems, as the Bode plot is independent of the amplitude of the input signal. However, due to the non-linear behaviour of pleated pneumatic artificial muscles, the system's gain becomes dependent on the amplitude of the input sine wave. As a result, only one Bode plot is insufficient to clearly describe or identify a non-linear system. In this study, the bandwidth of a muscle-valve system was assessed from two perspectives: a varying amplitude and a varying offset of the input sine wave. A brief introduction to pneumatic artificial muscles is given. The concept of pleated pneumatic artificial muscles is explained. Furthermore, the different test methods and experimental results are presented.